Detection of cylindrospermopsin and its decomposition products in raw and cooked fish (Oreochromis niloticus) by analytical pyrolysis (Py-GC/MS). (April 2020) - Prieto, Ana I.; Guzmán-Guillén, Remedios; Jos, Ángeles; Cameán, Ana M.; de la Rosa, José Ma; González-Pérez, José A.
Abstract: The presence of the toxin cylindrospermopsin is increasingly frequent in samples from different ecosystems and it is a serious problem both at environmental level and for animal and human health. To be able to prevent CYN exposure risk, it is important to have suitable analytical methods, but also quick and economical ones. Analytical pyrolysis coupled to GC/MS (Py-GC/MS) represents an important alternative for the rapid detection, characterization or "fingerprinting" of different materials. However, it has been less studied with cyanotoxins up to date. The present work aims to investigate: 1) the suitability of Py-GC/MS for detection of CYN and its decomposition products in raw and cooked fish samples before consumption and 2) the influence of the different cooking methods on the presence of different CYN degradation products detected by Py-GC/MS. For first time, these results present that Py-GC/MS could be a rapid and economical alternative for the detection and monitoring of CYN and its degradation products (DP. m/z 290.1, 169.1 and 336.2) in raw or cooked fish. Moreover, the changes induced in CYN and DP by cooking could be amenable and detected by Py-GC/MS. Highlights: Analytical pyrolysis has potential for CYN detection in fish samples. CYN decomposition products ( m/z 290.1, 169.1 and 336.2) can be detected. Cooking modified the abundance of CYN and its degradation products in fish. Boiling decreased the relative abundance of CYN in fish.